A combined antral and corpus rapid urease testing protocol can increase diagnostic accuracy despite a low prevalence of Helicobacter pylori infection in patients undergoing routine gastroscopy. Issue 5 (October 2015) - Parihar, Vikrant; Holleran, Grainne; Hall, Barry; Brennan, Denise; Crotty, Paul; McNamara, Deirdre
Background: The effects of an increased risk of sampling error and the lower prevalence of Helicobacter pylori infection on the diagnostic accuracy of standard invasive tests needs to be considered. Despite evidence of enhanced yield with additional biopsies, combined Rapid Urease Tests (RUTs) have not been widely adopted. We aimed to compare the diagnostic efficacy of a combined antral and corpus rapid urease test (RUT) to a single antral RUT in a low prevalence cohort. Methods: Between August 2013 and April 2014 adult patients undergoing a scheduled gastroscopy were prospectively recruited. At endoscopy biopsies were taken and processed for single and combined RUTs, histology and culture using standard techniques. Infection was defined by positive culture or detection of Helicobacter like organisms on either antral or corpus samples. Results: In all 123 patients were recruited. H. pylori prevalence was low at 36%, n = 44. There was a significant difference in positivity between single and combined RUTs, 20% ( n = 25) versus 30% ( n = 37), p = 0.0094, (95% CI 0.15–0.04). The number needed to treat (NNT) for an additional diagnosis of infection using a combined versus a single RUT is 4 (95% CI 2.2–11). The only factor associated with a reduction in RUT yield was regular proton pump inhibitor (PPI) use. Overall the sensitivity, specificity, positive and negative predictive value for any RUT test was 84%, 100%, 100% and 92% respectively. Conclusion: Our data suggests taking routine antral and corpus biopsies in conjunction with a combined RUT appears to optimizing H. pylori detection and overcome sampling error in a low prevalence population.